ANALISIS MINAT BELI KONSUMEN COFFEE SHOP DI BANDUNG - Khoerul Imam, Fahrul; Purwanti, Neulis Lia; Maya Sari, Nur; Permadi, Canra (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2024)
The growth of the Food & Beverage business, especially coffee shops, in Bandung City shows a significant increase along with the consumptive lifestyle of the community. In this context, this study aims to identify and analyze the influence of factors such as product quality, price, promotion, and location on consumer buying interest in coffee shops in Bandung City. The sample is part of the total number of characteristics included in the population. The sampling technique is a saturated sample, so that the entire population of 58 people is sampled. Primary data is obtained from questionnaires distributed to 58 respondents who have purchased coffee at a coffee shop. Secondary data is obtained from previous studies, various other references related to research variables and theories presented by experts. The method used by researchers in this study is a questionnaire. The rapid growth of the coffee shop industry in Bandung, Indonesia, is influenced by the dominance of consumers aged 15-45 years who visit the place 1-2 times a month, with the main considerations on price, product quality, and atmosphere.